2002
DOI: 10.1007/bf02850267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diclofenac sodium on union of tibial fractures in rats

Abstract: Nonsteroidal anti-inflammatory drugs are often used for 7 to 10 days after fracture because of their effects on bone metabolism. This study evaluated the effect of diclofenac sodium, administered at clinical dosage and duration, on bone union. Fifty-four male Wistar rats were randomly and equally divided into three groups: control, diclofenac 1 mg, and diclofenac 2 mg. Closed diaphyseal fractures were induced in the right tibias of all rats; the two diclofenac groups received intramuscular injections in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
0
19
0
8
Order By: Relevance
“…Most studies using osteotomy and bone ingrowth models have demonstrated that indomethacin and ibuprofen treatment retards bone healing [29,33,34,35,36,37,38,48,53,54]. In contrast, only a few studies indicate that NSAIDs have little or no effect on fracture healing outcomes [55,56,57,58,59,60]. One study concluded that indomethacin treatment had no effect on cortical bone healing following a small drill hole defect (2 mm in diameter) [61].…”
Section: Nsaid Effects On Experimental Models Of Bone Healingmentioning
confidence: 99%
“…Most studies using osteotomy and bone ingrowth models have demonstrated that indomethacin and ibuprofen treatment retards bone healing [29,33,34,35,36,37,38,48,53,54]. In contrast, only a few studies indicate that NSAIDs have little or no effect on fracture healing outcomes [55,56,57,58,59,60]. One study concluded that indomethacin treatment had no effect on cortical bone healing following a small drill hole defect (2 mm in diameter) [61].…”
Section: Nsaid Effects On Experimental Models Of Bone Healingmentioning
confidence: 99%
“…Considerable experimental evidence has indicated that conventional non-selective NSAIDs (indomethacin, ibuprofen, naproxen, ketorolac) have inhibitory effects on long bone fracture healing (2,3,13) although an absence of this deleterious effect has also been reported (27)(28)(29)(30). It has been suggested that factors such as dosage and duration of treatment could affect the results, as well as intra-and inter-species differences regarding sensitivity to drugs, compensatory local and systemic factors, rate of bone remodeling and pharmacokinetics of drugs in laboratory animals compared to humans (3,29).…”
Section: Potential Risks and Benefits For Bone Due To Prolonged Use Omentioning
confidence: 99%
“…In contrast, other studies suggest that NSAIDs have no signifi cant effect on bone repair or that their effects can only partially be attributed to the inhibition of PG synthesis [89,92,[96][97][98][99][100]. For example, no effects on collagen synthesis, an important marker of bone healing, were observed in vitro in rat fracture callus [101].…”
Section: Effects Of Non-selective Nsaids On Bone Healingmentioning
confidence: 99%